Effectiveness of Public Services at the Regional Education Office of North Sulawesi Province - Margareth I. R. Rantung,; Christina V. Ester,; Indrasatya Octavianus Nasirun,; Stince Sidayang,; Anastasya Mandagi, (Technium Social Sciences Journal, 2024)
This research aims to determine the effectiveness of employee salary management services at the North Sulawesi Provincial Education Office. The method used in this research is a qualitative method with data collection techniques through interviews, documentation and observation. This research focuses on the Effectiveness of Public Services at the Regional Education Office of North Sulawesi Province. Data collection techniques include; observation, interviews, and documentation. The research results show that: 1) Suitability and Efficiency of Service Process: Practices in the field are not in accordance with Standard Procedures, causing slow completion and unclear information. 2) Service Quality and Employee Engagement: Employees are less responsive and efficient, with slow responses and unsatisfactory solutions. 3) Facilities and Infrastructure: Lack of facilities, including limited service space and technical problems such as slow computers and unstable networks.